Sinergitas Edukasi Remaja Anti Napza BNN Provinsi Aceh Melalui Pendidik Sebaya: Study Komunikasi Duta Anti Narkoba - Fitrianti F; Zamzami Z; Rizki Maulida; Juaris J (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Drug, psychotropic, and addictive substance (NAPZA) abuse among adolescents is a serious problem that requires effective prevention strategies tailored to adolescents’ characteristics. This study aims to analyze the communication model used by the Anti-Drug Ambassadors of the Aceh Provincial National Narcotics Agency (BNNP Aceh) as peer educators in disseminating information and educating adolescents about the dangers of NAPZA in Aceh. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews with Anti-Drug Ambassadors as peer educators, adolescent recipients of the educational programs, and BNNP Aceh officials, as well as documentation. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the Anti-Drug Ambassadors of BNNP Aceh employ a persuasive communication model through a soft-approach strategy tailored to the characteristics and needs of adolescents. This strategy is implemented through communicative, engaging, firm, and interactive delivery of educational materials using ice-breaking activities, games, quizzes, videos, and both formal and informal educational activities. Education is conducted through both offline and online channels, utilizing social media platforms such as Instagram, TikTok, and YouTube, as well as conventional media. The implementation of these educational activities is supported by collaboration between BNNP Aceh and various government institutions, universities, schools, and communities as part of the P4GN strategy (Prevention and Eradication of Drug Abuse and Illicit Drug Trafficking). However, limited human resources and funding remain major challenges in expanding the reach of anti-drug education throughout Aceh.